To Do or Not to Do? Task Control Deficit in Obsessive-Compulsive Disorder. Issue 5 (September 2017) - Kalanthroff, Eyal; Henik, Avishai; Simpson, Helen Blair; Todder, Doron; Anholt, Gideon E.
Abstract: Task control is an executive control mechanism that facilitates goal-directed task selection by suppressing irrelevant automatic "stimulus-driven" behaviors. In the current study, we test the hypothesis that less efficient task control in individuals diagnosed with obsessive-compulsive disorder (OCD) is associated with OCD symptoms, and specifically, with the inability to inhibit unwanted behaviors in OCD. Thirty-five healthy controls, 30 participants with OCD, and 26 participants with generalized anxiety disorder (GAD) completed the object-interference (OI) task to measure task control, the stop-signal task to measure response inhibition, and the arrow-flanker task to evaluate executive abilities not contingent upon task control. OCD patients, but not GAD patients or healthy controls, exhibited impaired performance on the OI task. The deficit in task control, but not in response inhibition, correlated with OCD symptom severity. We suggest that reduced task control may be one of the neurocognitive processes that underlie the inability to inhibit unwanted behaviors in OCD. Highlights: Stimuli can evoke the performance of a task that has a strong association with it Task control is an executive mechanism aimed to suppress stimulus-driven behaviors Impaired task control, evident in OCD patients, correlated with symptom severity Response inhibition and interference control were not impaired in OCD patients We suggest that reduced task control is associated with OCD symptoms